Integrated modules for management of stem and root rot of sesame - Lalita Lakhran; R.R. Ahir; Namrata; Neelam Geat (Annals of Arid Zone, 2025)
The field investigation was conducted over two consecutive kharif seasons in 2018 and 2019 for management of stem and root rot of sesame. The study included treatments with fungicides, plant extracts, bio-agents, organic amendments, and their combinations, with each treatment being replicated three times. Eight protective and systemic fungicides were used. Carbendazim + mancozeb application provided maximum disease control (74.05%) and highest yield (446.50 kg ha-1) followed by application of carbendazim alone which provided 65.16% disease control and resulted in yield of 434.00 kg ha-1. Among eight phyto-extracts, garlic clove extract was found best with maximum disease control of 57.23% and yield of 394.50 kg ha-1 followed by neem leaf extract with 49.85% disease control and 370.50 kg ha-1 yield. Eight fungal and bacterial bio-agents were also evaluated in which Trichoderma viride 1 was best. Six organic amendments were tested against the disease under field conditions. Among these, Neem cake was found best with 50.80% disease control and 395.00 kg ha-1 seed yield followed by vermi compost with 44.94% disease control and 362.50 kg ha-1 of yield. Amongst different integrated disease management modules, seed treated with 10% aqueous solution of garlic clove @ 2g kg-1 seed followed by foliar spray of carbendazim + mancozeb resulted in maximum disease control (81.63%) with highest seed yield (472 kg ha-1).